EFEKTIVITAS PRAKTIKUM KANCING GENETIKA TERHADAP HASIL BELAJAR PSIKOMOTORIK PESERTA DIDIK PADA MATERI PEWARISAN SIFAT - Eka Apriyanti; Herlina Herlina; Adriani Adriani (Guru Membangun, 2023)
The concept of inheritance of traits in living things is one of the biology materials that students learn in class IX. Based on the results of interviews with students at Makassar National Junior High School, many students experience difficulties and misconceptions in understanding the concept of genetics (inheritance of traits), such as the misunderstanding of genotive and phenotypic traits that are considered the same. Genetic button practicum is used to facilitate students in understanding the concept of the material taught. This research aims to determine the effectiveness of genetic button practicum on students' psychomotor learning outcomes in inheritance material in SMP Nasional Makassar. The design used in this research is the design of One-Shot Case Study.  While the sample of this research is the class IX B SMP Nasional Makassar by the number of students is 33 students.  Determination of the sample was conducted using simple random sampling technique. The instrument used in this study is in the form of a guide sheet practicum and performance assessment. The results of the analysis show that the first practice is classical completeness 88% and the ratio of classical effectiveness is 117.3% and in the second practicum the classical completeness is 85% and the ratio of effectiveness is classically 113.3%. This means that the use of genetic button practical is effective in the psychomotor abilities of student in learning biology in inheritance material at SMP Nasional Makassar.